Scientific bases for the preservation of the Hawaiian crow (National Academy Press, 1992)
The Hawaiian Crow, or 'Alala, once an inhabitant of large forested areas of Hawaii, is now found only in the wild in a relatively small area of the central Kona coast. The decline of the 'Alala is part of a larger phenomenon of reduction and extinction of forest birds throughout Polynesia that has been associated with human colonization. It is a symptom of underlying ecological problems. In this book, a committee of experts in ornithology, captive propagation, conservation biology, population genetics, and ecology analyzes existing data about the 'Alala and details its findings, conclusions, and recommendations concerning recovery efforts for this endangered bird.